The folate catabolic process, its implications for folate requirement in humans and its antibacterial drug function - Quinlivan, Eoin P. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2001)
The one-carbon cycle, of which folate is the predominant constituent, is a major carrier of one-carbon units for biochemical synthesis, and is thought to be the sole mechanism of methyl-group transfer. It is involved both in purine and pyrimidine biosynthesis, in the regulation of transcription and epigenics, and in the synthesis of important biological compounds.
Keywords: Clinical Medicine, M.D.; Ph.D. Trinity College Dublin